Revitalizing Nusantara Traditions through Interactive Cultural Experiences with Augmented Reality Technology - Dawis, Aisyah Mutia; Setiyanto, Sigit; Sadida, Irfan; Bariq, Faiq Fadhil Dzulfiqar (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2024)
Advances in digital technology are opening up new opportunities for cultural preservation and promotion. Augmented Reality (AR), with its ability to blend the real and digital worlds, has the potential to bridge the gap between younger generations and the rich cultural heritage of the Nusantara. This research aims to develop an AR application called "Imersi Budaya Nusantara" Immersion into Nusantara Culture to revitalize Nusantara traditions through interactive and educational cultural experiences. The application is expected to increase interest and understanding of Nusantara culture among younger generations while serving as an example of utilizing technology for cultural preservation. The research utilizes the Model Development Life Cycle (MDLC), which includes the stages of concept, design, material collection, development, testing, and distribution. The application's content includes visualizations of traditional dances, houses, food, clothing, and music from various regions in Indonesia. The "Imersi Budaya Nusantara" application has been successfully implemented and tested. The results of functionality and usability testing indicate that the application performs well and is user-friendly. User experience evaluations, based on questionnaires, demonstrate high levels of engagement, enjoyment, and educational value. This research proves that AR technology is effective in increasing interest and understanding of Nusantara culture among the younger generation. The "Imersi Budaya Nusantara" application serves as a model for utilizing technology for cultural preservation, opening up opportunities for further development and related research.